ANALYSIS ABILITY OF MATHEMATICAL CONNECTION OF SMP STUDENTS IN COMPARATIVE MATERIAL IN REVIEW OF GENDER DIFFERENCES - Lianawati, Indah; Purwasih, Ratni (Universitas Negeri Makassar, 2018)
Mathematics is a science that can not be separated from other science as well as in everyday life. The ability of mathematical Connection aims to connect the mathematics with other disciplines and also daily life so that math can be more meaningful. This study aims to determine the ability of mathematical connections of junior high school students VIII class in one of junior high school in Bandung on Comparable material reviewed through gender. Subject consists of 35 students. In addition, the discussion on the mathematical connection ability for junior high school students from the difference of gender, between students and students in terms of ability penyimannya. The understanding of the mathematical connection capability rests on the concept of